Unsettling the Settlers: The Impact of the #RhodesMustFall Student Movement on White Student Consciousness at the University of Cape Town - Humphreys, Katharine Morgan (Department of Political Studies, 2023)
In March 2015 UCT student Maxwele Chumani hurled faeces at British Imperialist Cecil Rhodes' statue at the University of Cape Town in South Africa as an act of protest against institutionalised racism and lack of transformation since apartheid. Chumani's action sparked a wider student protest movement, calling for the decolonisation of UCT and higher education in South Africa more broadly under the banner of #RhodesMustFall (RMF). RMF brought large-scale disruption to UCT's academic year and the lives of its students with a range of peaceful, disruptive and violent methods of protest. Previous scholarship on #RhodesMustFall in the South African context focuses on the ideologies, student leaders and strategies of the movement, leaving a gap in the literature with regards to its impact, especially on white students. This thesis therefore, through semistructured interviews with white South African UCT students, explores the impact of the RMF movement on white racial consciousness at UCT. The study has a particular focus on white students' attitude towards the movement and how it influenced their understanding of, and attitude towards, race, racial injustice and their own white racial identity. White students' responses to RMF vary and while largely progressive included some reactionary elements. White student membership of racially diverse social groups was found to facilitate performative attitude change through iterative dialogues provoked specifically by the RMF protests. All respondents reported that they subsequently conformed to new campus norms regarding ‘acceptable' attitudes and race more broadly. The extent to which new values were meaningfully internalised remains uncertain, but the persistence of performative change over a four-year period suggests that expression of support for RMF and its ideologies, while performative, can be considered a form of identity change and therefore be seen as part of a conscientisation process.